Interactive Multimedia Tutorial of Discovery Learning Model (iMTDLM); Improving Pre-Service Physics Teachers’ Pedagogical Competence - Saprudin Saprudin; Nurdin Abdul Rahman; Fatma Hamid (Universitas Khairun, 2022)
This study aims to develop an interactive multimedia tutorial of discovery learning model (iMTDLM) and to examine its effect on the improvement of pedagogical competence and the ability of pre-service physics teachers (PPTs) in constructing lesson plans. This development research follows the ADDIE model (Analyze, Design, Develop, Implement dan Evaluate). The instruments used include a validation sheet for iMTDLM product, an instrument for assessing pedagogical competence, and an instrument for evaluating lesson plans. The implementation phase involved 9 PPTs who were taking the course Teaching Practice 1 at a university in the city of Ternate. The results of the study showed that the iMTDLM was successfully designed by combining the use of Adobe Director 11 and Filmora software. The use of the iMTDLM in the Teaching Practice 1 course yields a positive effect on the improvement of pedagogical competence and the PPTs’ ability to construct lesson plans.